Identifying The Future: Exploring Lived Experiences of Non-Formal Education Teachers Using 21st Century Skills - Shamsa Kanwal,; Dr Tahira Bibi,; Shaista Anjum,; Muhammad Omer Mansoor,; Irshan Arif, (Al-Qanṭara, 2025)
This study explores the experiences of non-formal education teachers in Islamabad, Pakistan, focusing on the use and impact of 21st-century skills. The research aims to Identify the most common 21st-century skills among these teachers, investigate how these skills influence teaching methodologies and student learning outcomes. Determine the specific training needs of non-formal educators to enhance their 21st-century skills. It employs qualitative methods approach to achieve a comprehensive understanding. A purposive sampling strategy will be used to recruit a diverse group of non-formal educators from various regions within Islamabad and representing different program types (Basic, secondary and vocational skills). Semi-structured interviews were conducted with participants to explore their lived experiences, perceptions of their 21st-century skills, and how they integrate these skills into their teaching methodologies. Thematic analysis was conducted on the interview transcripts to identify recurring themes and patterns related to teachers' 21st-century skills, their application in the classroom, and perceived challenges. By analysis of the data from interviews, the research identified the most common 21st-century skills among non-formal educators in Islamabad are communication and digital skills but lacking in life skills. Most of the teachers aware about teaching methodologies and learning outcomes but wants to learn updated skills to teach more effectively. Furthermore, this study highlighted age and experience-based variations and program-specific considerations related to these skills. The findings shows there is a need to focuses on the development of targeted training programs tailored to the identified needs of non-formal educators, ultimately enhancing their ability to equip students with the critical skills they need to grow well in the 21st century.